Stadium General Scholars Talk at Universitas Ahmad Dahlan UAD discussed issues of circular economy and smart waste management in Malaysia and developed countries - Azizul Helmi, Sofian (UMPSA, 2024)
YOGYAKARTA, INDONESIA, 25 September 2024 – Universitas Ahmad Dahlan (UAD) recently hosted the CHEST X MECHAPRO Engineering Exchange student mobility programme, which involved 20 students from the Faculty of Chemical and Process Engineering Technology (FTKKP) and the Faculty of Engineering Technology Mechanical and Automotive (FTKMA) at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).